Rady dla ojców w tzw. „tablicach domowych” (Kol 3,21 i Ef 6,4) - Borek, Wacław (Verbum Vitae, 2011)
The household codes in which we find the advices given to fathers are the exegetes’ focus of attention since the time of Reformation. From this period on, on the basis of various criteria, one tried to define the genre of household codes and set them apart as a separate body in the New Testament literature. Following the particular topic which regards the exhortations addressed to pater familias, we analyzed two fragments contained respectively in the Letter to Colossians and in the Letter to Ephesians. To grasp the specificity of these instructions, embedded in an easily traceable and repeating scheme, one should start with finding the common characteristics of the said paraenetic texts. The analyses showed that a common factor is a universal rule based on the two mutually complementing elements: subordination and reciprocity having their source in the Wisdom literature of the Old Testament and the commandment of love. Having in mind the above mentioned rule and the Hellenistic culture in which the addressees of the instructions lived, we examined the command given in the Letter to Colossians. It constitutes a point of departure for the expanded, catechismal instructions contained in the Letter to Ephesians.